Performance of Carbide Lime Waste Mortar via 24 Hours Accelerated CO2 Curing - Adrina Rosseira Abu Talip; Nur Hafizah Abd Khalid; Abdul Rahman Mohd.sam; Zahraa Hussein Joudah; Rohaya Othman (International Journal of Integrated Engineering, 2024)
This paper examined the use of Calcium Lime Waste (CLW) as a cementitious material for early CO2 capture. CLW is mostly Calcium Hydroxide (Ca(OH)2) with high CaO concentration, excellent for CO2 capture. Ordinary Portland Cement (OPC) mortar contained CLW (0-40%) direct substitutions were investigated under physical properties (workability and density), mechanical properties (compressive strength) and CO2 capturing properties (carbonation thickness and CO2 uptake by Thermogravimetric Analysis (TGA)) and porosity properties (Mercury Intrusion Porosimetry (MIP)) within the first 24 hours of accelerated carbonation curing, compared to control sample. Results indicated that 30% was the optimum mix based on the workability, CO2 capture and strength. TGA showed the carbonation converted Ca(OH)2 to CaCO3. MIP indicated that CLW increased mortar porosity and reduced pore size relative to the control mortar. The study shows CLW can act as an effective CO2 absorbent towards sustainable development of the construction industry by reusing industrial waste and sequestering CO2.